Autonomous discovery of optically active chiral inorganic perovskite nanocrystals through an intelligent cloud lab - Jiagen Li (Nature Portfolio, 2020)
Synthetic platforms coupled with artificial intelligent algorithms are highly desirable for advancing the discovery of new materials with target properties. Here the authors demonstrate the use of an autonomous laboratory for the discovery of optically active CsPbBr3 inorganic perovskite nanocrystals.